2020
DOI: 10.3390/cells9102197
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Promotes Mitochondrial Complex I Abundance via HIF-1α in Complex III and Complex IV Deficient Cells

Abstract: Murine fibroblasts deficient in mitochondria respiratory complexes III (CIII) and IV (CIV) produced by either the ablation of Uqcrfs1 (encoding for Rieske iron sulfur protein, RISP) or Cox10 (encoding for protoheme IX farnesyltransferase, COX10) genes, respectively, showed a pleiotropic effect in complex I (CI). Exposure to 1–5% oxygen increased the levels of CI in both RISP and COX10 KO fibroblasts. De novo assembly of the respiratory complexes occurred at a faster rate and to higher levels in 1% oxygen compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 84 publications
3
3
0
Order By: Relevance
“…Although Fis1 was also reported to play a role in mitochondrial fission [ 33 ], we found it was not affected by hypoxia ( Figure 5(a) ). In addition, we reported in hippocampal neurons hypoxia-induced Drp1 expression was due to hypoxia-sensitive transcription factor HIF-1 α ( Figure 6(a) ), which was consistent with previous publications carried out in fibroblasts [ 30 ], cardiac cells [ 22 ], and vascular smooth muscle cells [ 34 ]. Although other transcription factors such as Smad2/3 [ 35 ], NF- κ B [ 36 ], and calcium-related transcription factors [ 37 ] have been reported to correlate with Drp1 expression, we demonstrated that HIF-1 α inhibitors could almost completely inhibit hypoxia-induced Drp1 expression ( Figure 6(b) ), and thus, suggesting the pivotal role of HIF-1 α .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although Fis1 was also reported to play a role in mitochondrial fission [ 33 ], we found it was not affected by hypoxia ( Figure 5(a) ). In addition, we reported in hippocampal neurons hypoxia-induced Drp1 expression was due to hypoxia-sensitive transcription factor HIF-1 α ( Figure 6(a) ), which was consistent with previous publications carried out in fibroblasts [ 30 ], cardiac cells [ 22 ], and vascular smooth muscle cells [ 34 ]. Although other transcription factors such as Smad2/3 [ 35 ], NF- κ B [ 36 ], and calcium-related transcription factors [ 37 ] have been reported to correlate with Drp1 expression, we demonstrated that HIF-1 α inhibitors could almost completely inhibit hypoxia-induced Drp1 expression ( Figure 6(b) ), and thus, suggesting the pivotal role of HIF-1 α .…”
Section: Discussionsupporting
confidence: 92%
“…also reported to play a role in mitochondrial fission [33], we found it was not affected by hypoxia (Figure 5(a)). In addition, we reported in hippocampal neurons hypoxiainduced Drp1 expression was due to hypoxia-sensitive transcription factor HIF-1α (Figure 6(a)), which was consistent with previous publications carried out in fibroblasts [30], cardiac cells [22], and vascular smooth muscle cells [34].…”
supporting
confidence: 92%
See 1 more Smart Citation
“…It has recently been reported that low oxygen levels stabilized HIF-1α and increased CI levels. Meanwhile, knockdown of HIF-1α abrogated the effect of hypoxia on CI levels ( 31 ). Here, we showed that PPARG can function as a transcription activator for CI genes.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that HIF and hypoxiarelated pathways play critical roles in the development and progress of RCC (26,(29)(30)(31). Small molecule inhibitors that target HIF are promising therapeutical agents for RCC.…”
Section: Discussionmentioning
confidence: 99%